2020
DOI: 10.1007/s10834-020-09741-5
|View full text |Cite
|
Sign up to set email alerts
|

Disability and Household Welfare in Ghana: Costs and Correlates

Abstract: Persons with disabilities face substantial barriers that impede their integration and participation in social and economic activities. Households with disabled members may be vulnerable to poverty due to the extra cost of living with a disability. However, there exists a knowledge gap in the magnitude of the extra cost of disabilities in sub Saharan Africa. Using data from a nationally representative household survey, this paper estimates the extra cost of disabilities in Ghana. The paper further examines the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 41 publications
0
10
1
Order By: Relevance
“…Previous studies, including a systematic review, support this finding, showing that living with a household member with a disability entails high costs and poverty implications for the household [38,39]. These households must spend as much as 26% more to obtain an equivalent standard of living compared to those without disabilities [38,39]. Adolescents in our sample living with a head-of-household with disabilities reported themselves poorer, with much more diminished resources, and saddled with caregiving responsibilities that adversely affect their well-being compared to their peers in household headed by a person without disabilities.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Previous studies, including a systematic review, support this finding, showing that living with a household member with a disability entails high costs and poverty implications for the household [38,39]. These households must spend as much as 26% more to obtain an equivalent standard of living compared to those without disabilities [38,39]. Adolescents in our sample living with a head-of-household with disabilities reported themselves poorer, with much more diminished resources, and saddled with caregiving responsibilities that adversely affect their well-being compared to their peers in household headed by a person without disabilities.…”
Section: Discussionmentioning
confidence: 71%
“…Adolescents living with head-of-household with disabilities reported lower benefits from these potential accelerators in the areas of no poverty, informal cash transfers, good health, and no disability health access restrictions than their peers living with head-ofhousehold without disabilities. Previous studies, including a systematic review, support this finding, showing that living with a household member with a disability entails high costs and poverty implications for the household [38,39]. These households must spend as much as 26% more to obtain an equivalent standard of living compared to those without disabilities [38,39].…”
Section: Discussionmentioning
confidence: 80%
“…Previous studies, including a systematic review, support this finding showing that living with a household member with a disability had high cost and poverty implications for the household [38,39]. These studies concluded that households must spend as much as 26% more resources to obtain an equivalent standard of living compared to those without disabilities [38,39]. Adolescents in our sample living with household heads with disabilities reported themselves poorer, may have had much more diminished resources and saddled with caregiving responsibilities adversely affecting their well-being than their peers living with household heads without disabilities.…”
Section: Discussionmentioning
confidence: 73%
“…Adolescents living with household heads with disabilities reported lower benefits from these accelerators in no poverty, informal cash transfers, good health, and no disability health access restrictions than those living with household heads without disabilities. Previous studies, including a systematic review, support this finding showing that living with a household member with a disability had high cost and poverty implications for the household [38,39]. These studies concluded that households must spend as much as 26% more resources to obtain an equivalent standard of living compared to those without disabilities [38,39].…”
Section: Discussionmentioning
confidence: 80%
“…In 2005, the government established the Disability Fund to help reduce poverty among disabled people in the informal sector performing low‐paid and unskilled jobs that offer little or no career advancement. Yet, many were unaware of the existence of such a fund (Asuman et al, 2020). Ghana's disability policies have not been fully translated into practical outcomes to improve the lives of disabled people.…”
Section: Introductionmentioning
confidence: 99%